Utilização de Resíduo de Construção e Demolição Reciclado (RCD-R) para estabilização de um solo da cidade de Caxias do Sul - RS - Spigolon, Caroline Cichin (My University, 2021)
Civil construction is a major generator of solid waste, which, if incorrectly disposed, can harm the environment and human health. Recycled Construction and Demolition Waste (RCDW) can be incorporated into the soil in paving works as long as it meets the requirements of CBR, expansion and material characteristics requested in NBR 15115 (ABNT 2004b). In this work, the feasibility of using R-CDW to stabilize a soil in the city of Caxias do Sul, RS, was analyzed. The soil used for this study was Solo Forqueta, present in the city of Caxias do Sul, and the RCDW used was collected in a waste collection and processing company also in Caxias do Sul, RS. The soil was submitted to tests of density of the grains, granulometry, liquid limit, plastic limit, compaction and CBR; the RCDW was submitted to tests of density of the grains and granulometry. The Soil-RCDW mixtures tested were 15 %, 25 % and 35 % of substitution in mass, these mixtures were submitted to tests of density of grains, granulometry and CBR. In order to be able to use RCDW as recycled aggregate, it must also be classified as to its hazardousness, ensuring that it does not contaminate the environment or human beings. The studied waste is not hazardous, the material was classified by NBR 10004 (ABNT, 2004a) as Class II B waste, being non-hazardous and inert, and classified by CONAMA Resolution No. 307 (2002) as I - Class A waste. to the CBR and expansion test, the Soil-RCDW mixtures of 15 % and 25 % can be used in subgrade reinforcement works as they present CBR and expansion values consistent with those requested in NBR 15115 (ABNT 2004b), provided that it is better processing of the material was carried out, increasing the percentage of material passing through the sieve by 0.42 mm to meet the standard requirements. The percentage of replacement by mass of 25% of RCDW to the soil is the best alternative of those studied, as it meets the requirements requested in NBR 15115 (ABNT 2004b) for use in subgrade reinforcement and allows the use of a greater amount of RCDW, giving destination for a greater amount of waste. [resumo fornecido pelo autor]
A construção civil é uma grande geradora de resíduos sólidos, que, se descartados incorretamente podem prejudicar o meio ambiente e a saúde humana. O Resíduo de Construção e Demolição Reciclado (RCD-R) pode ser incorporado ao solo em obras de pavimentação desde que atenda aos requisitos de CBR, expansão e características do material solicitados na NBR 15115 (ABNT 2004b). Neste trabalho foi analisada a viabilidade de uso de RCD-R para estabilização de um solo da cidade de Caxias do Sul, RS. O solo utilizado para este estudo foi o Solo Forqueta, presente no município de Caxias do Sul, e o RCD-R utilizado foi coletado em uma empresa de coleta e beneficiamento de resíduos também de Caxias do Sul, RS. O solo foi submetido a ensaios de massa específica dos grãos, granulometria, limite de liquidez, limite de plasticidade, compactação e CBR; o RCD-R foi submetido a ensaios de massa específica dos grãos e granulometria. As misturas de Solo-RCD ensaiadas foram de 15 %, 25 % e 35 % de substituição em massa, estas misturas foram submetidas a ensaios de massa específica dos grãos, granulometria e CBR. Para que seja possível utilizar o RCD-R como agregado reciclado, também deve-se fazer a classificação do mesmo quanto à sua periculosidade, assegurando-se de que não seja contaminante ao meio ambiente ou ao ser humano. O resíduo estudado não apresenta periculosidade, o material foi classificado pela NBR 10004 (ABNT, 2004a) como resíduo de Classe II B, sendo não perigoso e inerte, e classificado pela resolução CONAMA Nº 307 (2002) como resíduo I - Classe A. Quanto ao ensaio de CBR e expansão, as misturas de Solo-RCD de 15 % e 25 % podem ser utilizadas em obras de reforço do subleito pois apresentam valores de CBR e expansão coerentes com os solicitados na NBR 15115 (ABNT 2004b), desde que seja realizado um melhor beneficiamento do material, aumentando o percentual de material passante na peneira de 0,42 mm para atender o solicitado em norma. O percentual de substituição em massa de 25 % de RCD-R ao solo é a melhor alternativa das estudadas, pois atende os requisitos solicitados na NBR 15115 (ABNT 2004b) para utilização em reforço de subleito e possibilita a utilização de maior quantidade de RCD-R, dando destinação para uma maior quantidade de resíduo. [resumo fornecido pelo autor]
Keywords: Engenharia civil; Resíduos como material de construção; Reaproveitamento (Sobras, refugos, etc.); Solos - Caxias do Sul (RS)